DEVELOPMENT OF AN ENGLISH TEXTBOOK FOR THE ECONOMICS PROGRAM AT GDE PUDJA MATARAM - Gede Eka Puja Dyatmika; Putu Ade Resmayani; Ida Bagus Made Arjana (University of Kuningan, 2025)
This research aims to: 1) Identify the development stages of the English language introduction textbook for the Economics Study Program, Semester II at IAHN Gde Pudja Mataram for the 2018/2019 academic year; 2) Assess the feasibility of the textbook based on expert evaluations; 3) Measure student responses to the developed textbook. This research employs the Research and Development (R&D) method with five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires and interviews. The results show that: 1) The development of the textbook was conducted through five systematic stages; 2) The quality of the textbook was rated very well, with high evaluations from both experts 1 and 2; 3) Student responses to the textbook were very positive, indicating good acceptance.This research presents novelty in the development of a textbook tailored to the needs of the Economics Study Program, involving validation by subject matter experts and student feedback. The five-stage methodology used provides a structured, need-based approach, enhancing the textbook's relevance in the learning context.